Three-dimensional movement analysis on forehand throws on sub-elite Ultimate Frisbee athletes - Leong, Kai Fong (Nanyang Technological University, 2021)
Frisbee throwing is essential to the sport Ultimate Frisbee as it is the only way to move the disc from one place to another. Currently, there is little information about the biomechanics of frisbee throws to help players improve their technique. Therefore, this study aims to explicitly determine the factors that make up an optimal forehand throw by using a three-dimensional movement analysis. 14 sub-elite male Ultimate Frisbee athletes were asked to perform 20 maximal effort forehand throws. three-dimensional movement analyses captured horizontal velocity of the right finger (RFIN) and right forearm (RFRM) markers, and elbow joint angle. The longest 30 throws (mean = 56.5m) were executed with higher peak horizontal velocity of both RFIN (6.78m/s > 5.72m/s) and RFRM (4.32m/s > 3.62m/s) markers, as well as sharper elbow joint angle (66.2⁰ < 71.7⁰) as compared to the shortest 30 throws (mean = 39.4m). The findings suggest that longer throws have higher peak horizontal velocity of the wrist and forearm, and sharper elbow angle than shorter throws among sub-elite athletes. However, it was observed that individuals possess different bodily motions, which might interact with the variables differently. Future research can explore comparing bodily motions and throwing techniques rather than the throws themselves.